2015
DOI: 10.4238/2015.may.18.22
|View full text |Cite
|
Sign up to set email alerts
|

Clinical analysis of patients with myeloperoxidase antineutrophil cytoplasmic antibody-associated vasculitis

Abstract: ABSTRACT. This prospective study analyzed the clinical characteristics of myeloperoxidase antineutrophil cytoplasmic antibody (MPO-ANCA)-associated vasculitis and explored the relationship between MPO-ANCA and clinical manifestations of the associated vasculitis in 132 p-ANCA and MPO-ANCA-positive patients (average age, 62.3 ± 14.8 years) who were initially diagnosed with ANCA-associated vasculitis. The p-ANCA and MPO-ANCA levels in peripheral blood were detected in all patients. Among these, 128 (97%) had mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 21 publications
(31 reference statements)
2
16
0
2
Order By: Relevance
“…Older patients were more likely to show lung involvement in the early disease stage in Japan [6]. This tendency is compatible with European patients [2].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Older patients were more likely to show lung involvement in the early disease stage in Japan [6]. This tendency is compatible with European patients [2].…”
Section: Discussionsupporting
confidence: 74%
“…According to the guideline for IP [5], basically all IP cases are recommended to examine serum ANA, MPO-ANCA, PR3-ANCA and other autoimmune antibody as a routine screening test to exclude the collagen vascular disease from IIPs. In the elderly, other symptoms such as hearing loss, recognition impairment, and cerebral infarction often disturb the definite diagnosis which will be taken several months [2]. Therefore, improving awareness and vigilance regarding this disease is important for early diagnosis and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that in consistency with studies from Western countries, AAV could affect people of all ages, with elderly people being more susceptible, and the kidneys and lungs were the most vulnerable organs [8,9]. In our referral diagnostic center in Peking University First Hospital, over 200 new patients with AAV are diagnosed annually; this indicates that AAV is not rare in Chinese [10].…”
Section: Prevalence Of Aav In Chinamentioning
confidence: 53%
“…Compared with younger patients, older patients were more likely to suffer from MPA than GPA [16]. It was found that pulmonary involvement was more prevalent and more severe in older patients than in younger ones [9,16]. Those findings indicated that patients with different ages might have different susceptibility to variant disease entities and organ involvement of AAV.…”
Section: Prevalence Of Aav In Chinamentioning
confidence: 87%
“…In a series of 85 MPA patients only 10% had pericarditis, cardiac failure occurred in 18%, and MI in 2% [48]. In another Chinese cohort cardiac involvement was present in one-fifth of the patients, with pericardial involvement (pericarditis and pericardial effusion), cardiomyopathy, aortic incompetence, and rhythm disturbances being described [49].…”
Section: Cardiac Manifestation In Microscopic Polyangiitismentioning
confidence: 99%